Diseases of wild birds in southern Rio Grande do Sul, Brazil - Echenique,Joanna V.Z. (2020)
ABSTRACT: Necropsy protocols of the “Laboratório Regional de Diagnóstico” of “Faculdade de Veterinária” of the “Universidade Federal de Pelotas” were reviewed, ranging the period from 2000 to 2018. Three hundred eighty one necropsies, 25 refrigerated and/or formaline fixed organs, and seven biopsies were received, representing 413 samples. Most of these materials were sent by the “Núcleo de Reabilitação da Fauna Silvestre” of “Universidade Federal de Pelotas” (NURFS-CETAS-UFPel) and were from municipalities within the range area of LRD-UFPel influence. Of the 413 cases 55 (13.31%) corresponded to metabolic/nutritional diseases; 50 (12.10%) to trauma; 35 (8.47%) to bacterial diseases/toxi-infections; 30 (7.26%) to parasitic diseases; 28 (6.77%) to fungal diseases; four (0.97%) to viral diseases and 17 (4.11%) to other diseases. Cases where it was not possible to determine the etiology, were in severe autolysis or were inconclusive totaled 194 (46.97%). Metabolic/nutritional diseases and traumatic injuries were the main cause of death in wild birds’, being Passeriformes the most affected order.